Northern Ireland after the troubles : a society in transition - Coulter, Colin, 1966-; Murray, Michael (Michael J.) (Manchester University Press, 2008)
The work sets out to challenge the official reading that the troubles are now over and that the future of Northern Ireland will almost inevitably be one of prosperity and progress. It is a critical response to the choreographed optimism that defines both official discourse and media commentary on Northern Ireland.